Analytical Characterization for Similarity Assessment Between an Aflibercept Biosimilar SB15 and Reference Product (Eylea®) - Hangyeore Lee; Jongcheol Huh; Dayoung Kim; Soye Lee; Jaeil Lee; Jungmin Lee; Beom Chan Kim; Jinsu Song (Ophthalmology and Therapy, 2024)
Abstract Introduction SB15 is a proposed biosimilar product of reference aflibercept (Eylea®), an approved biological drug product for retinal diseases including neovascular age-related macular degeneration (nAMD). This study aimed to assess the analytical similarity between SB15 and its commercially available reference product (RP) sourced from the United States (US-aflibercept) and European Union (EU-aflibercept) in terms of structural, physicochemical, and biological properties. Methods A panel of state-of-the-art analytical methods was used for the comprehensive characterization of SB15 and US/EU-aflibercept. In terms of the structural and physicochemical properties, primary structure; post-translational modifications (PTM); higher-order structure; purity and impurities; charge variants; and glycosylation were compared. In addition, biological characterization including mechanism of action (MoA)-related and Fc-related biological activities was conducted. Results Analytical similarity between SB15 and US/EU-aflibercept was demonstrated. The primary and higher-order structure of SB15 was confirmed to be comparable to that of US/EU-aflibercept. In addition, there were no meaningful differences in the physicochemical properties in terms of size and charge heterogeneity between SB15 and its RP. SB15 and RP were similar in biological activities including MoA-related binding activities, potencies, and Fc-related biological functions. Consequently, SB15 was confirmed to be highly similar to US/EU-aflibercept. Conclusions Based on a comprehensive analytical similarity assessment of structural, physicochemical, and biological properties, SB15 was demonstrated to be highly similar to US/EU-aflibercept RP, supporting safe and effective use of SB15.